Dapagliflozin pada Gagal Jantung dengan Fraksi Ejeksi Rendah (HFrEF): Tinjauan Sistematis Mekanisme dan Efektivitas Klinis - Karmawan, Zalfa Nadia Prasasti; Simorangkir, Rahel Lambok Yohana; Kalalo, Jef Gishard Kristo (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Heart failure with reduced ejection fraction (HFrEF) is a serious condition associated with high morbidity and mortality. Dapagliflozin has demonstrated cardioprotective effects in patients with HFrEF. Objective: This review explores the mechanisms underlying the clinical benefits of dapagliflozin and summarizes current evidence from the DAPA-HF trial and its sub-analyses regarding its effectiveness in patients with HFrEF. Methods: Relevant literature was systematically searched in PubMed, Google Scholar, and Scopus. Eligible studies were analyzed using a narrative approach to summarize the drug’s mechanisms of action and clinical outcomes. Results: Dapagliflozin improves cardiac energy efficiency, stimulates erythropoiesis, reduces myocardial fibrosis, and lowers oxidative stress and NT-proBNP levels. Clinically, 10 mg/day therapy reduces heart failure hospitalizations and cardiovascular mortality by 26% (HR: 0.74), with recently hospitalized patients experiencing benefits up to 49% (HR: 0.51), consistent across subpopulations and providing added advantages to standard therapy. Conclusion: Dapagliflozin serves as an effective adjunct therapy for HFrEF, offering rapid and sustained benefits, reducing morbidity and mortality, and improving patients’ quality of life. Further research is warranted to expand its clinical application.